Troubleshooting Plantwide Oscillations using Nonlinearity Information (Journal of Chemical Engineering, 2010)
Plant-wide oscillations are common in many processes. Their effects propagate to many units and mayimpact the overall process performance. It is important to detect and diagnose the cause of suchoscillations in order to rectify the situation and maintain the proper profitability of the plant. This paperproposes a new procedure to detect and diagnose plant-wide oscillations using routine operating data. Themethod has been developed based on the nonlinearity information in the process data. A new TotalNonlinearity Index (TNLI) has been defined to quantify nonlinearities. The method is based on theassumption that the nonlinearity is highest near the source and decreases as one moves away from thesource. This assumption is true because chemical processes have the nature of low-pass filters and theyfilter out gradually higher order harmonics of the signals. Signals with higher order harmonics aregenerally more nonlinear. The proposed diagnostic method has already been successfully applied fortroubleshooting many industrial plant-wide oscillation problems. Two of such case studies have beenpresented in this paper.Journal of Chemical Engineering Vol.ChE 24 2006 50-60